RETRACTED: Mathematical tools for updating the value profile of environmental university programs’ students - Ivashova Valentina; Zolotarev Sergey; Ardashev Roman; Kovaleva Svetlana; Aboneeva Catherine; Kalashova Anna (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001